1989
DOI: 10.1007/bf00373137
|View full text |Cite
|
Sign up to set email alerts
|

Activation of K+ currents in cultured Schwann cells is controlled by extracellular pH

Abstract: We analyzed the pH dependence of K+ currents recorded with the patch-clamp technique from cultured Schwann cells obtained from mouse dorsal root ganglia. Currents were activated at potentials more positive than -50 mV which was close to the resting membrane potential. Current amplitudes were affected by a change in extracellular pH (pHo), being increased at alkaline, and decreased at acidic pHo. The strongest effect of a pHo change was observed on currents activated close to the resting membrane potential sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 27 publications
7
23
1
Order By: Relevance
“…9B). Contrary to results in rabbit and rat cultured Schwann cells (Howe & Ritchie, 1989) and similarly to Hoppe, Lux, Schachner & Kettermann, (1989) in the same preparation as ours, no sign of an inward Na+ current was found with this protocol in any of the twenty-five cells tested. Among the different criteria proposed by Hagiwara & Byerly (1981) for identifying voltage-dependent Ca21 channels, are listed: persistence of the signal when Ca2+ in the external solution is replaced by Ba2+ or strontium (Sr2+), insensitivity of the signal to high concentrations of tetrodotoxin (TTX) and blockage of the signal by Co2+.…”
Section: Lack Of Na+ Current In Mouse Schwann Cellscontrasting
confidence: 92%
See 1 more Smart Citation
“…9B). Contrary to results in rabbit and rat cultured Schwann cells (Howe & Ritchie, 1989) and similarly to Hoppe, Lux, Schachner & Kettermann, (1989) in the same preparation as ours, no sign of an inward Na+ current was found with this protocol in any of the twenty-five cells tested. Among the different criteria proposed by Hagiwara & Byerly (1981) for identifying voltage-dependent Ca21 channels, are listed: persistence of the signal when Ca2+ in the external solution is replaced by Ba2+ or strontium (Sr2+), insensitivity of the signal to high concentrations of tetrodotoxin (TTX) and blockage of the signal by Co2+.…”
Section: Lack Of Na+ Current In Mouse Schwann Cellscontrasting
confidence: 92%
“…1987 (Shrager et al 1985), rabbits (Chiu et al 1984) and mice (Konishi, 1989a). In the same preparation as ours, Hoppe et al (1989) reported the presence of voltage-dependent and pH-sensitive K+ currents. According to differences in voltage dependence, inactivation kinetics and pharmacological properties, we conclude that mouse Schwann cells in our cultures display two types of K' currents.…”
Section: Discussionsupporting
confidence: 67%
“…Conversely, in non-inactivating channels the mean open probability continuously increased with depolarization. The heterogeneity in time-dependence of single channel behaviour is also reflected in a heterogeneity of whole cell currents recorded from different Schwann cells (Hoppe et al, 1989). Eighty-four percent of cells inactivated, and the time constant of inactivation and its voltage dependence were similar to the values obtained from averaged single channel recordings (Fig.…”
Section: Time Dependent Gating Properties Of Single K + Channelsmentioning
confidence: 78%
“…In opossum kidney cells, inwardly rectifying K+ channels were activated by a more alkaline pH (Ohno-Shosaku, Kubota, Yamaguchi & Fujimoto, 1990): the potassium current of cultured Schwann cells was also inhibited by external H+ (Hoppe, Lux, Schachner & Kettenmann, 1989). All these channels were influenced by changes within the physiological pHi range, whereas in the cardiac KATP channel, it was blocked by a strong acidic pHi below 6-0.…”
Section: Effects Of H+ On Katp Channels In Atp-free Solutionmentioning
confidence: 97%